SELF-REGULATED LEARNING GUIDANCE BASED TO DEVELOP THE CHARACTER OF PGSD STUDENTS - Darmiany Darmiany (Universitas Brawijaya, 2022)
This study aims to develop and test the effectiveness of character strengthening guidance for PGSD students based on self-regulated learning. The development research design is used for model development by involving subjects from PGSD students, and academic supervisors. Self-regulated learning-based character guidance is directed to encourage students to apply the principles of self-regulated learning in their learning. It is proven that this model can improve student learning patterns in harmony with the principles of self-regulated learning and increase learning achievement.